Plasmapheresis in the Treatment of Neurologic Disorders in Bangladesh: A Review Update (Journal of National Institute of Neurosciences Bangladesh, 2017)
Plasmapheresis is a very effective modality of treatment for many of the immune-mediated neurological disorders. It is a relatively new concept in the context of our country. Although it was previously done in one or two of the private hospitals but the expense was beyond the affordability of m59ost of our patients. Since its inception on September, 2012 the National Institute of Neurosciences & Hospital (NINS) has made some major advancement in patient management. Initiation of plasmapheresis at an affordable cost is one such example. In this article we intend to share our experience of the few cases who have received this treatment. Journal of National Institute of Neurosciences Bangladesh, 2015;1(2): 62-64